Utilizing Household Waste Turning Household Waste into Economically Valuable Products to Train Teacher Entrepreneurship in Junior High Schools in Tegal Regency - Subali, Bambang; Ellianawati, Ellianawati; Yulianti , Ian; Listiyanto, Listiyanto; Raharjo, Tri Joko; Setyaningsih , Natalia Erna; Nurdiana, Fitri; Fitriasari , Diah Nur; Pangestuti, Rahayu; Vannesa, Leni (Universitas Negeri Semarang, 2024)
Students' ability to conduct scientific activities, including research, problem-solving, and decision-making based on Pancasila values, needs to be enhanced through the implementation of the Pancasila Student Profile Strengthening Project (P5). This community service aimed to train teachers and students in utilizing used cooking oil to create economically valuable aromatherapy candles, fostering entrepreneurial skills. The methods included training and mentoring involving 43 science teachers of the MGMP in Tegal Regency as change agents. The results demonstrated that participants successfully understood the techniques for processing used cooking oil into aromatherapy candles, marketing products via social media, and innovating packaging. The conclusions revealed that the training effectively enhanced participants' understanding of transforming household waste into economically valuable products, aligning with character education and entrepreneurial development.